Expografia na contemporaneidade: propostas em arte e tecnologia digital - Boelter, Valeria (2016)
This paper discusses the practice and theory of expography an art exhibition and digital technology. It is based on the experiences of this author, as an exhibitions designer, in conjunction with the research on the history, theory and criticism of art. It presents the development of a design through procedural strategies, techniques and exhibition to discuss exhibition with digital technology in the field of art. This research analyzes some pioneering exhibitions in art and digital technology, takes some practice and conceptions in the area from experience and analysis to perform the expography FACTORS 1.0 and FACTORS 2.0.